Characterization of natural low transition temperature mixtures (LTTMs): Green solvents for biomass delignification - Yiin, Chung Loong; Suzana, Binti Yusup; Quitain, Armando T.; Mitsuru, Sasaki; Yoshimitsu, Uemura; Tetsuya, Kida (Elsevier Ltd., 2016)
The aim of this work was to characterize the natural low transition temperature mixtures (LTTMs) as promising green solvents for biomass pretreatment with the critical characteristics of cheap, biodegradable and renewable, which overcome the limitations of ionic liquids (ILs). The LTTMs were derived from inexpensive commercially available hydrogen bond acceptor (HBA) and L-malic acid as the hydrogen bond donor (HBD) in distinct molar ratios of starting materials and water. The peaks involved in the H-bonding shifted and became broader for the OH groups. The thermal properties of the LTTMs were not affected by water while the biopolymers solubility capacity of LTTMs was improved with the increased molar ratio of water and treatment temperature. The pretreatment of oil palm biomass was consistence with the screening on solubility of biopolymers. This work provides a cost-effective alternative to utilize microwave hydrothermal extracted green solvents such as malic acid from natural fruits and plants.